Molecular characterization and SNP identification using genotyping-by-sequencing in high-yielding mutants of proso millet - Francis, Neethu; Rajasekaran, Ravikesavan; Rajagopalan, Veera Ranjani; Bakya, S. Vinothini; Muthurajan, Raveendran; Kumar, Ashwini Girish; Alagarswamy, Senthil; Krishnamoorthy, Iyanar; Thiyagarajan, Chitdeshwari (Frontiers in Plant Science, 2023)
Proso millet (Panicum miliaceum L.) is a short duration, C4 crop that is drought tolerant, nutritionally rich and can grow well in marginal lands. Though the crop has many climate resilient traits like drought and heat tolerance, its yield is lower than common cereals like rice, wheat and maize. Being an underutilised crop, the molecular resources in the crop are scarce. The objective of the present study was to develop and characterise high yielding mutants in proso millet. Gamma irradiation induced mutant population was screened to identify high yielding mutants which were evaluated upto M4 generation. One mutant with dense panicle and high yield (ATL_hy) and one with lax panicle and low yield (ATL_ly) along with wild type was sequenced using Genotype-By-Sequencing approach. The variants detected as SNPs and InDELs were annotated against the reference genome of proso millet. Bioinformatic analyses using NCBI and Uniprot databases were done to elucidate genetic information related to the SNP variations. For both mutants maximum functional SNPs occurred on chromosome 13. The total number of functional SNPs identified in high yielding and low yielding mutants were 84 and 171 respectively. Two functional SNPs of low yielding mutant have occurred in the sequence coding for the enzyme starch synthase which is involved in starch biosynthetic pathway. This information can be further used in identifying genes responsible for various metabolic processes in proso millet and in designing useful genetic markers.